2015
DOI: 10.1002/jclp.22242
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Edged Sword: A Review of Benefits and Risks of Online Nonsuicidal Self-Injury Activities

Abstract: Given the double-edged effect of online NSSI activities, clinicians may benefit from incorporating clients' online NSSI activity in the context of NSSI assessment and treatment. Future research ought to directly examine the link between online NSSI activity and NSSI behavior to better understand the nature of these benefits and risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
131
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(141 citation statements)
references
References 37 publications
(138 reference statements)
8
131
2
Order By: Relevance
“…This notion is further supported by a recent study, stating that one third of youth (14 to 25 years) with a history of NSSI reported online help-seeking for NSSI [34]. Therefore, the online activity regarding NSSI can be viewed as beneficial (e.g., decreasing social isolation, receiving encouragement for recovery, reducing urges to self-injure) or potentially harmful (e.g., triggering urges to self-injure, social reinforcement of NSSI) [35]. Future research will have to explore which measures need to be taken in order to use the beneficial potential of online resources while restricting harmful consequences.…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
“…This notion is further supported by a recent study, stating that one third of youth (14 to 25 years) with a history of NSSI reported online help-seeking for NSSI [34]. Therefore, the online activity regarding NSSI can be viewed as beneficial (e.g., decreasing social isolation, receiving encouragement for recovery, reducing urges to self-injure) or potentially harmful (e.g., triggering urges to self-injure, social reinforcement of NSSI) [35]. Future research will have to explore which measures need to be taken in order to use the beneficial potential of online resources while restricting harmful consequences.…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
“…As a result, a large number of participants had engaged in frequent and varied NSSI, and the sample is not representative of general or clinical populations. Findings may, however, be clinically relevant given evidence that young people with NSSI have higher internet usage than their peers (Mitchell & Ybarra, ); in one year, more than 42 million internet searches regarding self‐injury were made (Lewis, Mahdy, Michal, & Arbuthnott, ); and that recent research has suggested the importance of clinicians assessing internet usage in those with NSSI (Lewis, Heath, Michall, & Duggan, ; Lewis & Seko, ) due to the potential for harm and benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the prior research has been very similar, in that it has focused on investigating the benefits and risks of posting about NSSI behaviors and pro-NSSI Instagram pages. Some studies have taken a balanced approach; on the one hand, they list the benefits of reducing social isolation and finding social support, while on other hand they also find that posting NSSI activity can invite reinforcement of NSSI or triggering NSSI urges (Lewis & Seko, 2015).…”
mentioning
confidence: 99%
“…There have been studies conducted that explore the possible consequences users face for posting their personal NSSI on social media. In a meta-analysis exploring the risks and benefits of online posting of NSSI, Lewis and Seko (2015) found major themes in NSSI social media involvement. Their study found that one possible reason that people who utilize NSSI post on social media is to connect with others who are going through similar experiences.…”
mentioning
confidence: 99%